2019
DOI: 10.1021/acs.langmuir.8b02642
|View full text |Cite
|
Sign up to set email alerts
|

Gas Adsorption at Metal Sites for Enhancing Gas Sensing Performance of ZnO@ZIF-71 Nanorod Arrays

Abstract: The detection of trace amount of volatile organic compounds (VOCs) has been covered by tons of researches, which are dedicated to improve the detection limit and insensitivity to humidity. In this work, we have synthesized ZnO@ZIF-71 nanorod arrays (NRAs) equipped with the adsorption effect at metal site that promoted the detection limit of ethanol and acetone, to which also have great selectivity. The gas sensor not only exhibits shorter response/recovery time (53/55% for ethanol, 48/31% for acetone), but als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…[80,91], while ZIF-71 is used to detect larger gas molecules (e.g., ethanol, acetone, etc.) [95]. In addition, although ZIF-71 is slightly less insensitive to humidity than ZIF-8, it can still be used to reduce the cross-sensitivity of water vapor [80].…”
Section: Selection Of Composite Materials With Smox and Mofmentioning
confidence: 99%
See 1 more Smart Citation
“…[80,91], while ZIF-71 is used to detect larger gas molecules (e.g., ethanol, acetone, etc.) [95]. In addition, although ZIF-71 is slightly less insensitive to humidity than ZIF-8, it can still be used to reduce the cross-sensitivity of water vapor [80].…”
Section: Selection Of Composite Materials With Smox and Mofmentioning
confidence: 99%
“…Gas permeation through the MOF consists of three steps: (1) adsorption of the gas in the MOF, (2) diffusion of the gas within the MOF, and (3) desorption [108]. The enhancement of gas adsorption may also contribute to the gassensitive performance, as evidenced by the study of Zhou et al [95]. They synthesized ZnO@ZIF-71 nanorod arrays, and found that compared with pure ZnO, it has better selectivity for ethanol and acetone, and its response is also improved.…”
Section: Exploration Of the Types Of Detection Gasesmentioning
confidence: 99%
“…Reliable methods to facilitate real‐time monitoring of toxic gases are urgently needed. Recently, gas sensors have attracted extensive attention for their role in monitoring the atmospheric environment, medical diagnosis, volatile organic compounds (VOCs) and toxic gases [2a,b,c,d,e] . For example, in terms of environmental monitoring, ZnO sensors can be used to detect industrial exhaust emissions and automobile exhaust (eg: NOx, SOx, COx) [1a,3] .…”
Section: Introductionmentioning
confidence: 99%
“…In non‐invasive medical diagnosis, the ZnO sensor can detect the concentration of H 2 S and acetone in human breath to determine the disease, such as halitosis and diabetes [2b,4] . The metal oxides semiconductor (MOS) gas sensor was widely investigated owing to its high response, low production cost and long‐term stability [2d,5] …”
Section: Introductionmentioning
confidence: 99%
“…Generally, the physical and chemical performances of semiconductor nanocrystals can be minutely adjusted by their shape and exposed crystal faces, which determine the arrangement and coordination of the surface atoms. Thus, the shape and crystal facet-controlled synthesis of semiconductor nanocrystals draw considerable research interest. As an essential p-type semiconductor, the CuCo 2 O 4 nanocrystal has extensively been investigated due to its high conductivity, nontoxicity, corrosion resistance, low cost, and potential applications in Li-ion batteries, supercapacitors, electrocatalysis, photocatalysis, fuel cells, magnetism, and gas sensors. However, little research has been conducted on the influence of exposed crystal planes on performance.…”
Section: Introductionmentioning
confidence: 99%